Assessing Genetic Diversity Cocoa (Theobroma cacaoL.) Collection Resistant to Cocoa Pod Borer Using Simple Sequence Repeat Markers - Agung Wahyu Susilo; Dapeng Zhang; Lambert Motilal (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2013)
Breeding  for  cocoa  pod  borer  (CPB)  resistance  on  cocoa  was  initiated  by selecting  the  resistant  genotypes  through  cocoa  farm  in  the  endemic  area.  For breeding  purpose  the  collected  genotypes  should  be  assessed  for  their  diversity  in  constructing  appropriate  mating  design.  This  research  has  objective  to assess  genetic  diversity  of  the  exploratory  collection  using  DNA  fingerprinting. The  tested  clones  were  25  exploratory  collections  compared  to  the  references  of seven  international  clones  from  International  Cocoa  Genebanks,  Trinidad  and12 national clones. DNA of the tested clones was sequenced using 15 SSR markers at Sustainable Perennial Crop Laboratory of Beltsville Agriculture Research Center.Data of  fingerprinting were analyzed  using  GenAlEx program  to  perform number of  alleles,  observed   heterozygosity  (Ho),  expected  heterozygosity  (He)  and genetic  distance.  The  tested  clones  performed  high  genetic  diversity  with  the number  of  alleles  was  98  (6.53  per  locus)  compared  to  the  national  clones  andinternational clones were  95 (6.33 per locus) and 86 (5.73 per locus), respectively. The  observed  heterozygosity  of  the  tested  clones  (Ho  = 0.63)  was  higher  thannational  clones  (Ho  =  0.60)  and  international  clones  (Ho  =  0.49)  then  supported by  the  expected  heterozygosity  (He)  of  the  tested  clones  (He  =  0.71)  also  highin  equal  value  with  international  clones  (He  =  0.74).  Cluster  analysis  grouped the  tested  clones  to  three  main  genetic  groups,  namely  Trinitario,  Forastero  and unidentified  group.  The  CPB-resistant  clones  of  ARDACIAR  10  and  KW  397 were clustered in different group that indicate a far distance of their genetic background.Key words:Genetic diversity, cocoa, CPB resistance, simple sequence repeat marker.